Entering Discourses: A New Agenda for Qualitative Research and Sociology of Knowledge - Keller, Reiner (Qualitative Sociology Review, 2012)
The article argues for a new agenda in qualitative research and sociology of knowledge. It starts with the assumption that meaning-making activities which lie at the heart of sociology’s interpretative paradigm today are widely embedded in expert proceedings and organized or institutionalized work on symbolic ordering. This holds true for the sciences or other specialized discourse realms (like religion), but it also counts for public discourses/public arenas. While interpretative traditions in sociology have addressed issues of discourse research, they did not succeed in establishing a proper sociological approach to discourse. Therefore, the article proposes a sociology of knowledge approach to discourse (SKAD), located in the social constructivist tradition of Peter L. Berger and Thomas Luckmann. Such an approach is able to account for discourses as processes of symbolic ordering and to take up questions of discourse research raised by French philosopher Michel Foucault. Foucault indeed insisted on discourses as “truth games” and activities which set up knowledge claims. But, this interest in politics of knowledge has not so far been taken up in today’s arenas of discourse research. Therefore, SKAD proposes concepts and procedures for a new agenda of sociology of knowledge, deeply committed to qualitative and interpretative research traditions in sociology.